2010
DOI: 10.1080/00291951.2010.528224
|View full text |Cite
|
Sign up to set email alerts
|

Rule-based GIS-modelling for management purposes: A case study from the islands of Froan, Sør-Trøndelag, mid-western Norway

Abstract: The coastal heath region along the western coast of Norway, dominated by Calluna vulgaris, is undergoing rapid change. Vegetation changes are caused by changes in management, including reduced frequency or abandonment of periodic heath burning and reduced cutting and grazing. The islands of Froan, in the outermost part of Sør-Trøndelag County in mid-western Norway, are dominated by coastal heath in a state of recession due to reduced traditional land use. The coastal heath is acknowledged as vulnerable and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…In local studies, it has been documented that many of the above-mentioned areas have been deforested by various forms of land use lasting for millennias, whereas natural forest regeneration and afforestation in recent decades have evidently shown the ecological potential for forests in semi-natural heaths and meadows throughout Norway (Bryn, 2008;Bryn & Daugstad, 2001;Bryn et al, 2010;Hemsing & Bryn, 2011;Lundberg 2011;Måren, 2009;Moen et al, 2006;Øyen, 2008;Potthoff, 2009;Rö ssler et al, 2008). Similar findings have been reported from local studies in the European Alps and many other mountain regions, so the process of deforestation is probably more or less the same for populated mountain regions worldwide, although with large variations in the extent of deforestation (GehrigFasel et al, 2007;Rutherford et al, 2008;Sitzia et al, 2010;Slaymaker, 2010;Tasser et al, 2007).…”
Section: Gis Model Of Potential Forest Expansion In Norway 89mentioning
confidence: 99%
“…In local studies, it has been documented that many of the above-mentioned areas have been deforested by various forms of land use lasting for millennias, whereas natural forest regeneration and afforestation in recent decades have evidently shown the ecological potential for forests in semi-natural heaths and meadows throughout Norway (Bryn, 2008;Bryn & Daugstad, 2001;Bryn et al, 2010;Hemsing & Bryn, 2011;Lundberg 2011;Måren, 2009;Moen et al, 2006;Øyen, 2008;Potthoff, 2009;Rö ssler et al, 2008). Similar findings have been reported from local studies in the European Alps and many other mountain regions, so the process of deforestation is probably more or less the same for populated mountain regions worldwide, although with large variations in the extent of deforestation (GehrigFasel et al, 2007;Rutherford et al, 2008;Sitzia et al, 2010;Slaymaker, 2010;Tasser et al, 2007).…”
Section: Gis Model Of Potential Forest Expansion In Norway 89mentioning
confidence: 99%
“…RS-based classifications, on the other hand, describe the land surface at a specific point in time or changes through time (e.g. Arctic greening and browning) (Myers-Smith et al, 2020) and, accordingly, portray actual vegetation as influenced by previous and ongoing land use (Bryn et al, 2013). Depending on the modelling setup, DM may pragmatically describe the current ecological envelope of a target or aim at revealing the proximate causes for its distribution (Ferrier and Guisan, 2006), thus modelling either actual or potential natural vegetation, depending on the input data used for modelling (Hemsing and Bryn, 2012;Hengl et al, 2018).…”
Section: What Is Modelled By Dgvm Rs and Dmmentioning
confidence: 99%
“…The three study sites capture major parts of variation in vegetation regions, ranging from nemoral to high-alpine areas (Bakkestuen et al 2008), but the large site-specific differences in vegetation-type distributions and trajectories indicate that many more landscape regions preferably could be included. However, when our findings are compared with those of other spatio-temporal vegetation-type modelling studies elsewhere in Norway (Bryn 2008;Bryn et al 2010), as well as a potential forest model that covers entire Norway , the overall indication is that a major part of the vegetation in many rural districts is strongly structured by previous land use.…”
Section: How Representative Are the Study Sites For Norway?mentioning
confidence: 50%
“…In a similar study of a mountain region in south-east Norway, Bryn (2008) found that ∼50% of the terrestrial landscape was structured by land use. Further, from a study site in a nature reserve on the outer coastal region of rural midNorway, Bryn et al (2010) documented that up to ∼85% of the terrestrial landscape would change following landuse abandonment. We therefore believe that previous land use in Norway still affects a number of nature conservation areas and that such issues should be given more attention in nature management conservation plans than they presently receive (Lundberg 2002;Bryn et al 2010;Fjellstad et al 2010).…”
Section: Land-use Impact On Vegetationmentioning
confidence: 98%
See 1 more Smart Citation